Effect of Feeding Concentrate Mixture Containing Varying Levels of Cashew Nut Kernel Meal on Nutrient Utilization in Ram Lambs - Balaga, Sravani; Konka, Raja Kishore; Dhulipalla, Srinivas Kumar; Matha, Kalyana Chakravarthi (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted to assess the effect of feeding concentrate mixture containing varying levels of cashew nut kernel meal (CNKM) on nutrient utilization in ram lambs. Eighteen ram lambs were randomly divided into three equal groups of six each and allotted to three dietary treatments (T1 to T3) comprising of green fodder viz., Super Napier and concentrate mixture (20% CP) containing CNKM at 0, 10 and 20%, respectively. The average DMI of ram lambs was comparable among treatments. Significantly higher (P
Keywords: Concentrate mixture; Cashew nut kernel meal (CNKM); Nutrient digestibility; Ram lambs